2020
DOI: 10.1080/03050629.2021.1835890
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? The decision to flee or stay home during civil war

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…These pursuits to regain or sustain control over ancestral land, which sustains their desired immobility, also resulted in the persistence of eco-violence among the conflicting parties. This study addressed the concerns raised by scholars (Esparza et al, 2020;Marston, 2020;Braithwaite, Cox and Ghosn, 2021;Masullo, 2021, p. 889) regarding the neglected factors influencing and sustaining immobility in conflict-affected communities. This novel approach offers a fresh perspective on the factors that influence and sustain immobility among community members in ungoverned spaces affected by eco-violence.…”
Section: The Role Of Collective Memory In Shaping Immobility In the M...mentioning
confidence: 96%
“…These pursuits to regain or sustain control over ancestral land, which sustains their desired immobility, also resulted in the persistence of eco-violence among the conflicting parties. This study addressed the concerns raised by scholars (Esparza et al, 2020;Marston, 2020;Braithwaite, Cox and Ghosn, 2021;Masullo, 2021, p. 889) regarding the neglected factors influencing and sustaining immobility in conflict-affected communities. This novel approach offers a fresh perspective on the factors that influence and sustain immobility among community members in ungoverned spaces affected by eco-violence.…”
Section: The Role Of Collective Memory In Shaping Immobility In the M...mentioning
confidence: 96%
“…People decide to leave their countries, inter alia, as a result of various forms of violence, such as an open conflict, terrorist activities and persecution for various reasons, for example, on ethnic or religious grounds (forced migration) (Baláž et al, 2021; Braithwaite et al, 2021; Davenport et al, 2003; Donato & Massey, 2016; Turkoglu & Chadefaux, 2019). As research shows, in addition to being driven by direct hostilities, displacement is also caused by indirect violence.…”
Section: Theoretical and Historical Backgroundmentioning
confidence: 99%
“…Other approaches stress cultural and linguistic considerations (Suzuki, 2022), geographical factors (distance between the residence and target countries: Moore & Shellman, 2007) and historical aspects (previous linkages, e.g., colonial ties or being previously part of the same state: Havinga & Böcker, 1999; Neumayer, 2004). A special role is played by social networks, not only among economic migrants but also of refugees (Adhikari, 2012; Braithwaite et al, 2021; Lamba & Krahn, 2003), including those from Ukraine. Research (Varpina & Fredheim, 2022) has found that ties were the main motivation for the refugees who fled from Ukraine to Latvia.…”
Section: Theoretical and Historical Backgroundmentioning
confidence: 99%
“…An extraneous circumstance worth mentioning even though it is beyond the scope of this paper is armed conflict. With armed conflict, community members often either must flee or shelter in place with either reality increasing women's vulnerability to gender‐based violence including sexual violence from both intimate partners as well as armed militias (Braithwaite et al, 2021 ). The violence women frequently experience at the hands of specific institutions such as the military and law enforcement need to be taken into account in considering our approach to minimizing barriers to help seeking.…”
Section: Implications For Nursingmentioning
confidence: 99%